2014
DOI: 10.1111/ijd.12667
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional vs. contact cryosurgery in treatment of keloids: a clinical and immunohistochemical study

Abstract: Intralesional cryosurgery is superior to contact cryosurgery in terms of efficacy and safety. Both techniques may have beneficial effects on keloids, at least partially, through the modulation of VEGF and tenascin C expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The largest study reviewed contained 95 patients. 19 However, the median number of patients per study was 17. The published evidence base for this technique was uniformly Level 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest study reviewed contained 95 patients. 19 However, the median number of patients per study was 17. The published evidence base for this technique was uniformly Level 4.…”
Section: Resultsmentioning
confidence: 99%
“…Weshahy and Ebdel Hay, using a different cryoneedle to that popularised by Har-Shai, reported mean scar volume reductions of 93.5% in 20 patients at four months after treatment 18 and Abdel-Meguid et al, from the same centre, observed mean scar volume reductions of 61% following intralesional cryotherapy, compared with reductions of 23% with contact cryotherapy. 19 However, it is unclear if the effect persisted in the long term. Roitman et al reported in two patients persistence of 100% keloid scar reduction at six months following single procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment for keloids in general include intralesional corticosteroid and 5‐fluorouracil injections, silicone gel sheeting, pressure therapy, laser therapy, cryotherapy and surgical therapy followed by postoperative radiotherapy . Although there is no single definitive treatment modality for keloids, combinations of several therapeutic regiments can be used depending on the race, age and gender of the patient and the size, duration, location, colour, shape and symptoms of the keloid .…”
Section: Introductionmentioning
confidence: 99%
“…[4] The importance of VEGF in the development and exaggerated of hypertrophic scar and keloid had led to trials of medications with antivascular and antiangiogenesis properties. [5] Previous in vitro studies also suggested that corticosteroids can suppress the synthesis of VEGF. [6] Hence, modulation of VEGF production could comprise an appreciated treatment modality for keloids.…”
mentioning
confidence: 99%